Do professors favor liberal students? Examining political orientation appearance cues and professor bias - Woodzicka, Julie A.; Boudreau, Grace H.; Hayne, Sarah L. (Frontiers in Education, 2024)
The perception of political bias in higher education persists even in the face of scarce evidence that liberal professors penalize conservative students or favor liberal ones. We investigated the degree to which college professors used student appearance to ascertain political orientation, and whether liberal-looking students were rated more favorably. Ninety-eight (98) professors rated a student on logic, likeability, and political leaning. The hypothetical student’s dress (bohemian vs. business casual) and hairstyle (brown hair vs. pink hair) were manipulated to cue political orientation. Results indicated that professors used student appearance to ascertain liberal political leaning but did not rate the students significantly different on logic and likeability. These results suggest that while professors use appearance cues, they do not favor students who appear liberal leaning or punish those who look less liberal.